Some aspects regarding the quality of the accounting infirmation and its users - Dochev, M. (Економічний вісник Донбасу, 2010)
The accounting information is a corner stone when making appropriate managerial decisions and providing economic indicators to external contractors. To this end it is necessary that while keeping business accounts the enterprise should provide neutrality of the information coming from it, i.e., it should exclude one-sided gratification of the interests of certain groups of information users, if through a selection of a definite from of presentation it impacts the decisions and assessments made by them in view of reaching predetermined results and ramifications. Key words: accounting, information, quality, aspects. Облікова інформація — наріжний камінь для ухвалення відповідних директорських рішень і забезпечення економічних показників для зовнішніх контрагентів. Вона повинна виключити одностороннє задоволення інтересів певних груп інформаційних користувачів. Ключові слова: звітність, інформація, якість, аспекти. Учетная информация — краеугольный камень для принятия соответствующих директорских решений и обеспечения экономических показателей для внешних контрагентов. Она должна исключить одностороннее удовлетворение интересов определенных групп информационных пользователей. Ключевые слова: отчетность, информация, качество, аспекты.